Hukum Islam dan Akhlaq sebagai Pilar Utama dalam Manajemen Bisnis Islami - Edy, Sarwo (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2023)
Islamic law and ethics play a crucial role in shaping sustainable and ethical Islamic business management. Islamic law provides a clear framework for conducting business, while ethics strengthens the moral and ethical dimensions of business decision-making. This research examines the relationship between Islamic law, ethics, and Islamic business management, and its implications for contemporary business practices. In-depth analysis of Islamic legal sources and ethical values such as honesty, justice, and social responsibility reveals the importance of integrity and morality in every aspect of business. The findings shed new light on how the integration of Islamic law and ethics can enhance business performance and sustainability in the complex global economy.